PENGARUH PEMBELAJARAN EKONOMI ISLAM TERHADAP MINAT MAHASISWA MENABUNG DI BANK SYARIAH (Studi Pada Mahasiswa Program Studi Ekonomi Syariah STAI Sufyan Tsauri Majenang) - Masngudi Masngudi; Bella Agustina (J-EBI: Jurnal Ekonomi Bisnis Islam, 2021)
This study aims to investigate the influence of Islamic Economics study on  student interestsavings in Islamic banks, especially in the Economic Sharia students.  The research was conducted at STAI Sufyan Tsauri Majenang. The data source of this research using primary data and secondary data. The sampling technique in this  research is done by simple random sampling. These results indicate that the learning  of Islamic Economics on student interestsavings in Islamic banks, especially in the  Economic Sharia student STAI Sufyan Tsauri Majenang has apositive influence.The influence of Islamic Economics study on the interest savings in Islamic bank simplies that the greater understanding of the Islamic bank in the learning of Islamic Economics, the greater the savings in student interest in Islamic banks.Keywords: Islamic Economic Studies, Interest Savings, Bank Syaria